Stock charts for dummies - Schnell, Greg; Epstein, Lita (--For dummies., 2018)
Many trading and technical analysis books focus on how to use charts to make stock trading decisions, but what about how to actually build a chart? Stock Charts For Dummies reveals the important stories charts tell, and how different parameters can impact what you see on the screen. This book will explain some of the most powerful display settings that help traders understand the information in a chart to find outperformance as its beginning. Stock Charts for Dummies will teach you how to build a visually appealing chart and add tools based on the type of trading or investing decision you're trying to make. It will also introduce you to the pros, cons, and best practices of using three key types of charts: Candlesticks, Bar Charts, and Line Charts.--Publisher's description.